2015
DOI: 10.3747/co.22.2698
|View full text |Cite
|
Sign up to set email alerts
|

Pericardiocentesis versus Pericardiotomy for Malignant Pericardial Effusion: A Retrospective Comparison

Abstract: Background Treatment of malignant pericardial effusion remains controversial, because no randomized controlled

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 15 publications
3
29
0
2
Order By: Relevance
“…The sensitivity of pericardial fluid cytology ranges from 66.7% to 92%. This value depends heavily on the gold standard used per study (eg, follow‐up, pericardial biopsy, postmortem autopsy) but nevertheless is considered a valid and useful diagnostic tool 9, 16, 17, 18. Variation also exists between series on what should be classified as a definite malignant effusion; some authors consider cytology‐negative fluid as constituting a malignant effusion if the patient has a known malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of pericardial fluid cytology ranges from 66.7% to 92%. This value depends heavily on the gold standard used per study (eg, follow‐up, pericardial biopsy, postmortem autopsy) but nevertheless is considered a valid and useful diagnostic tool 9, 16, 17, 18. Variation also exists between series on what should be classified as a definite malignant effusion; some authors consider cytology‐negative fluid as constituting a malignant effusion if the patient has a known malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…This value depends heavily on the gold standard used per study (eg, follow-up, pericardial biopsy, postmortem autopsy) but nevertheless is considered a valid and useful diagnostic tool. 9,[16][17][18] Variation also exists between series on what should be classified as a definite malignant effusion; some authors consider cytologynegative fluid as constituting a malignant effusion if the patient has a known malignancy. In contrast with these analyses, we chose to limit malignant effusion to those with a proven positive cytology, as determined by a pathologist, and to classify cytology-negative patients as idiopathic in the absence of another plausible cause, even when they had an underlying cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The pericardial space can be invaded by direct tumor extension or metastatic spread via lymphatics or blood. Pericardial effusion can also develop as a result of chemotherapy, radiation therapy, or from opportunistic infections (47). …”
Section: Pericardial Diseasesmentioning
confidence: 99%
“…If pericardiocentesis is performed, the drain should be left in place for 3–5 days and surgical pericardial window should be considered if the output drainage is still high 6–7 days after pericardiocentesis. Effusions are more likely to recur with percutaneous pericardiocentesis compared with pericardiotomy, even though there was no difference in length of stay or ICU admission with either approach (47). …”
Section: Pericardial Diseasesmentioning
confidence: 99%
“…4 Other study involving malignancy cases showed that pericardiocentesis associated with higher recurrence rate as compared with surgical pericardiotomy, however the diagnostic yield and overall complication rate did not significantly differ. 5 Pericardiocentesis with pericardial drainage is safe and effective as the primary treatment for pericardial effusion in patients with malignancy. 6 Surgical drainage of the pericardium is superior to non-surgical approaches for symptom relief, reduced effusion recurrence and lower morbidity.…”
Section: Discussionmentioning
confidence: 99%